PRODUCTION OF POLYHYDROXYALKANOATE FROM USED COOKING OIL BY SOIL-ISOLATED BACTERIA - Pinyaphong, Porntippa (PSRU Journal of Science and Technology, 2021)
Polyhydroxyalkanoate (PHA) are synthesized and accumulated in bacterial cells to serve as an energy source. The objective of this research was to select bacteria capable of producing high PHA from soil contaminated with polycyclic aromatic hydrocarbons and to study the optimum conditions for producing PHA. Soil samples of 3 areas: the grass burning area, area contaminated with engine oil and area contaminated with agricultural chemicals were used for screening bacteria through Mineral Salt Medium (MSM) with 1%w/v glucose as a carbon source. PHA synthesis was preliminary tested by staining cells with Sudan Black B. It was found that 4 bacterial isolates were selected from 91 bacterial isolates. SCODw0.2 isolated from soil contaminated with engine oil was able to produce the highest PHA at 0.605 g/L (55.0% of dry cell weight). The optimum conditions of PHA synthesis from used cooking oil by SCODw0.2 were investigated. It was found that this isolate bacterium could produce highest PHA about 0.879 g/l (68.9% of dry cell weight) when cultured in MSM medium containing used cooking oil and ammonium sulphate as carbon source and nitrogen source, respectively, at ratio of 100 : 1, pH 7 and incubated at 35 °C for 60 hours. The composition of PHA that synthesized by bacteria when analyzed by gas chromatography-mass spectrometry was consisted of 3-hydroxydodecanoate, 3-hydroxytetradecanoate and others were 72.94, 12.92 and 14.14 %, respectively.